Effect of complex vs. repeated sprints training on repeated sprint ability and athletic performance in young elite soccer players - Buchheit, M.; Brughelli, M.; Delhomel, G.; Ahmaidi, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Repeated sprint (RS) ability (RSA) is related to maximal speed and metabolic-related factors (e.g., PCr recovery, H+ buffering) (Bishop et al., 2004). RS training has been shown to improve RSA in adult soccer (Bravo et al., 2008) and adolescent handball (Buchheit et al., 2008) players. Nevertheless, the respective impact of a strength/speed (aimed at improving maximal speed) vs. a `metabolic` (aimed at improving the ability to repeat sprints) training program is unknown. Thus the aim of the present study was thus to compare the effects of strength/speed vs. RS training on RSA in young elite soccer players. Methods Fourteen elite male adolescents (14.5±0.5 y; Tanner Stage III = 8, IV = 6; 64.1±7.7 kg; 1.77±0.9 m; 9 h.week-1 + 1 game) were assigned to either complex (C; n=7) or repeated sprint (RS; n=7) training groups. During 10 weeks; C consisted in 4 to 6 series of 4 to 6 exercises (e.g., counter movement jumps (CMJ), depth and plyometric jumps, agility drills, standing start and shuttle sprints), each repetition interspersed with at least 45 s of passive recovery; RS training consisted of 2-3 sets of 5-6 x 15-20 m shuttle sprints (interspersed with 14 s of passive or 23 s of active recovery [˜2 m.s-1 (Buchheit et al. 2008)]). The groups performed either C or RS once a week and maintained similar external training programs. Before and after training, performance was assessed by a CMJ, a hopping test (Hop), 10 and 30 m sprint times (10m and 30m), and best (RSAbest) and mean (RSAmean) times on a repeated shuttle sprint ability test (Buchheit et al. 2008). Results After training, except for 10m (P=0.22), all performances were significantly improved in both groups (all P<0.05). Relative changes in 30m (-2.1±2.0 %) were similar for both groups (P=0.45). C tended to induce greater improvements in CMJ (16.9±12.9 vs. 8.7±4.5 %, P=0.08, ES=0.9) and Hop height (27.5±19.2 vs. 13.5±13.2 %, P=0.08, ES=0.9) height compared with RS. In contrast, RS training induced greater improvement in RSAbest (-2.90±2.1 vs. -0.08±3.3 %, P=0.04) and tended to enhance more RSAmean (-2.61±2.8 vs. -0.75±2.5 %, P=0.10, ES=0.70) compared with C. Conclusion Both complex and repeated sprint training regimens represent effective means to increase physical performance in young elite soccer players. Nevertheless, changes in performance are likely training regimen-specific, with repeated sprint training being more effective at improving running performance (i.e., RSA) and complex training more effective at improving jumping ability.